Microstructural Linguistic Aspects in the Healing Mantras of the Sasak People - Gita Sarwadi; Deki Zulkarnaen (Lembaga Penelitian dan Pendidikan Mandala, 2026)
This study aims to describe the linguistic aspects that construct the microstructure of Sasak healing incantation texts (Mantra) . Microstructure is understood as internal linguistic elements that include lexical choice, grammatical forms, figurative language, as well as the use of repetition and parallelism in the text. This research employs a descriptive qualitative approach using critical discourse analysis as its method.The research data consist of Sasak healing Mantra obtained through observation, in-depth interviews with traditional healers, as well as recording and documenting the incantation texts. Data analysis was conducted through stages of transcription, classification of linguistic elements, and interpretation of meaning based on cultural context. The results show that the microstructure of Sasak healing mantra is dominated by archaic and religious diction, the use of imperative and declarative sentences, and stylistic features such as repetition, metaphor, and symbolism.These linguistic elements function to strengthen the suggestive and sacred power of the incantations in traditional healing practices. The linguistic aspects of microstructure not only serve as a means of linguistic expression but also as a medium for transmitting cultural values and beliefs of the Sasak community. This study is expected to enrich linguistic studies and oral tradition discourse as well as support efforts to preserve local culture.